Common agricultural policy Health Check: the beginning of CAP’s re-nationalization? - Marko LOVEC; Emil ERJAVEC (Acta Agriculturae Slovenica, 2011)
The article analyses Common agricultural policy (CAP) Health Check (HC) negotiations process and outcome. It proposes realist, structural economic model, based on Moravcsik’s liberal intergovernmental theory, which has distinct conceptual and methodological characteristics from major theoretical models on recent CAP reforms. Instead of focusing on institutionally embedded European policy-making, it is proposed that national interest articulation process is relatively autonomous, that common decisions are determined through two level distributional bargaining games and that policy changes are essentially underpinned by global development of competitive forces. Research is focused on formal statements and positions expressed by actors involved in the process, on economic rationale of different mechanisms and on CAP’s economic effects on different interest groups. Analysis which heavily draws from specialized first and second hand resources supports the proposed model. It is concluded that state-structured decision making and economic forces development are driving CAP reforms towards greater national flexibility in targeting and financing.